Remediation of Sound Wave Material Assisted by Sasando to Improve Understanding of Concepts and Analytical Thinking Abilities - Gelu, Afrianus; Marwoto, Putut; Aji, Mahardika Prasetya (Universitas Negeri Semarang, 2020)
Physics learning in sound wave material by utilizing sasando musical instruments is one of the learning experiences that allows students to develop cognitive, affective, and psychomotor abilities. Through sasando, sound material can be learned, for example the concept of factors that affect the frequency, resonance, and intensity of sound. The purpose of this study was to determine the effect of applying PBL learning models assisted by sasando musical instruments to the students understanding of concepts and analytical thinking ability. Data collection techniques are carried out through observation and tests. The results of data analysis showed that PBL learning strategies assisted by sasando musical instruments had an effect on students’ both conceptual understanding and analytical thinking ability. The results of the N-Gain pretest and posttest calculations in the experimental class showed an increase in understanding concepts and analytical thinking ability of students. The understanding concept of N-Gain value increases by 51.76% with the medium category, while the value of N-Gain analytical thinking increases by 52.95% with the medium category. In general, the conclusions that can be drawn from this study are PBL learning strategy strategies assisted by sasando musical instruments have a positive effect on understanding concepts and students' analytical thinking skills.